Omphalolith: An underdiagnosed entity. Issue 10 (11th October 2022) - Jouini, Wafa; Litaiem, Noureddine; Zaimi, Yosra; Mouelhi, Leila; Debbeche, Radhouane; Zeglaoui, Faten
Abstract: Omphalolith is a rare and underdiagnosed entity due to the accumulation of sebum and keratin in the umbilicus. It usually occurs in the elderly with deep and narrow umbilicus. Early recognition of omphalolith is important to prevent complications, unnecessary investigations, and anxiety. We report herein two new cases of omphalolith. Abstract : Omphalolith is an underdiagnosed entity due to the accumulation of sebum and keratin in the umbilicus. It mainly occurs upon elderly with deep and narrow umbilicus. A gentle extraction of the calculus using forceps allows the diagnosis and the treatment of this affection. Dermoscopy can be useful to rule out other diagnosis.